Land Access, Livelihood Diversification Strategies and Rural Household Well-Being in Mnquma, Eastern Cape: Implications to Extension Agents: Array - Mzuyanda, Christian (Acta Universitatis Danubius. Œconomica, 2020)
The objective of this paper is to analyse the impact of land access and livelihood strategies to well-being of households in Mnquma, Eastern Cape. A cross-sectional research design was utilised to collect data from 105 randomly selected households using a well-structured questionnaire. Descriptive statistics was then used to profile livelihood strategies and characteristics such as age, gender, years of farm experience, the availability of water and land for crop production and the income farmers generate from the sale of crops produced. Multinomial logistic regression results demonstrated that land size and location have a positive significant influence (p = 0.001) on household well-being. It is concluded that, though land size has a positive influence on well-being, expanding farms through adding plots and distant farming hinders the attainment of well-being. Moreover, households with large number of dependents and those working in exclusive farming are disadvantaged in the attainment of well-being. There is therefore room to enhance progress in attainment of well-being through reducing the distance to farms and promoting diversification of livelihood strategies. The Eastern Cape department of Agriculture and Rural Development is advised to support distant farmers with settlements in their destinations.